PURIFICATION OF DUG WELL WATER USING ACTIVATED CARBON MADE FROM SAGO FIBER WASTE - Desprianto Desprianto; Idawati Supu; Ika Suliawati; Juwita Juwita; Erfiana Erfiana (Jambura Physics Journal, 2021)
The sago fiber waste is promising as an active carbon material which has a high adsorption in purifying water process. The objective of this research was to make activated carbon from sago fiber waste to be applied for water purification and iron (Fe) adsorption with various of contact time. The carbon activation process uses Phosphoric Acid (H3PO4) and calcined at 800 °C for 2 hours. After drying, then analyzed the water content and ash content. Furthermore, surface morphology testing was carried out using SEM. The application of activated carbon was carried out in dig well water purification and filtering iron (Fe) based on variations in contact time of 10 minutes, 20 minutes, 30 minutes and 40 minutes. Analysis of water content of activated carbon was carried out 3 times with an average value of 3.9662%. Ash content analysis aims to determine the metal oxide content in activated carbon. Analysis of the ash content of activated carbon was carried out 3 times with an average value of 5.3239%. The average value of ash content meets the quality standards of activated carbon SNI 06-3730-1995 where the standard value of ash content for powdered activated carbon is a maximum of 10%. SEM test results show that the surface of the activated carbon is porous but the size is not uniform. The level of Ferrium (Fe) in water that has gone through the purification process using activated carbon. The most effective contact time was obtained, namely 20 minutes and had met the threshold requirements for water turbidity levels according to Minister of Indonesia health. This means that activated carbon from sago fiber is able to adsorb the material contained in water and also very capable in  picking up some bad contents of cloudy and polluted water.